La despersonalización como metafísica vivencial de la voluntad de vivir - Baquedano Jer, Sandra (Revista de Filosofía, 2010)
This article is about depersonalization as existential metaphysics of the will to live, stating that through phenomena associated with depersonalization it is possible to experience that not only are we knowing beings, but we are also things-in-itself in our interiors. From this experience, we will explore the possibility of becoming independently conscious from that noumenon of will, to capture the intimate essence of things, facing the will, which means, facing oneself. This is when the will to live stops being anonymous, finds its identity and begins the path of its denial.